Work Life Balance: Bagaimana Kepuasan Kerja dapat Memediasi terhadap Kinerja Karyawan - Nadia Grafi Fransiska; Ikhsan Maksum (Universitas Batanghari Jambi, 2023)
The research study conducted has the intention of understanding the role of job satisfaction in mediating Work Life Balance on employee performance at Bank BTN Syariah Malang City. The research method uses a quantitative approach, where later research will emphasize theory testing by measuring research variables numerically and requires statistical procedures for data analysis. The number of samples used in this study were organic employees (permanent employees) with a total of 64 people. The results and conclusions found are that work life balance has a direct significant positive effect on employee performance at Bank BTN Syariah Malang employees, work life balance has a direct significant positive effect on job satisfaction of Bank BTN Syariah Malang employees job satisfaction has a direct significant positive effect on performance employees of Bank BTN Syariah Malang employees, job satisfaction can mediate the effect of work life balance on employee performance on employees of Bank BTN Syariah Malang, and work life balance and job satisfaction are created so as to improve employee performance.